Uji Aktivitas Antibakteri Sabun Cair Ekstrak Metanol Daun Mangga Arum Manis (Mangifera indica L. var. arum manis) Terhadap Staphylococcus epidermidis - Afif Hussein Kholid Bahrisy; Laeli Fitriyati; Naelaz Zukhruf Wakhidatul Kiromah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Soap making has been done liquid soap preparation safer use of the nature ingridients anextract methanol leaves mango arum manis (Mangifera indica L. var. arum manis). Thekind of research this is experimental. Extract was obtained through means tektikmaceration with methanol solvent. Liquid soap made into three formulation with thevariation of concentration extract F1 7,81g/mL; F2 15,53g/mL; and F3 62.5g/mL then itwill be physical test and zone clear on Staphylococcus epidermidis bacteria with themethods sumuran, Control negative uses a base soap and control positive for the liquidsoap in circulation stood in line. The data obtained tested use of One Way ANOVA.This research result indicates that liquid soap formula 1, 2 and 3 meet physical evaluationpreparation except its viscosity and free alkali. Formula 1, 2 and 3 having antibacterialactivity zone each with a diameter of an obstruent 8,75mm; 10,6mm; and 12mm. Liquidsoap preparation formula 1, 2 and 3 having the difference meaningful and control positiveand negative control with a value of p<0.05. Liquid soap preparation antibacterial activityevery meaningful having the difference with p<0.05 percentage point. Variationconcentration extract methanol leaves mango (Mangifera indica L. var. arum manis) toaffect their antibacterial activity of Staphylococcus epidermidis. Formula 3 byconcentration of the extract 62,5g/ml antibacterial activity have the best compared to aformula 1 and 2.